MEREKA YANG DILUMPUHKAN: CITRA KULI DI DELI DALAM NOVEL BERPACU NASIB DI KEBUN KARET, KULI, DAN DOEKOEN KARYA MADELON SZEKELY-LULOFS - . Sudibyo (Humaniora, 2008)
Berpacu Nasib di Kebun Karet, Kuli dan Doekoen report the lives of extravagant white settlers in contrast to the fate of coolies regarded as retarded and subordinated natives. The three novels give historical accounts of the planter community in East Sumatra. They narrate thecoolies’ mishandling on the basis of the author’s involvement on the narrated world. Berpacu, Kuli and Doekoen represent the Dutch imperial exploitative practices in the first half of the 20th century on rubber plantations in East Sumatra. Berpacu, kuli and Doekoen place coolies as being animalized and marginalized other. The three novels add to the long series of Dutch colonial literature justifying exploitation and mastery. Based on focalization analysis, the narrator might owed considerably to the idea of marginalization and racialism because she merely narrated what she had seen without any critical thinking and any sympathy toward the fate of the coolies.